PENGARUH PEMBERIAN KOMBINASI MINERAL SELENIUM, ZINC, DAN VITAMIN E TERHADAP KUALITAS FISIK, KIMIA, DAN MIKROBIOLOGI DAGING BROILER - Ratna Ermawati; Muhammad Mirandy Pratama Sirat; Purnama Edy Santosa (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
Broiler meat could be a medium for the growth and development of microorganisms that could be the cause of meat spoilage. This study aimed to examine the effect of supplementation of the combination of the minerals Selenium, Zinc, and Vitamin E through drinking water on the physical, chemical, and microbiological quality of broiler meat. The study was conducted in May-October 2021. The treatment was given for 30 days in the broiler cage unit in Adimulyo Village, Gading Rejo District, Pesawaran Regency, Lampung Province. This research was using Completely Randomized Design with five treatments and three replications (five tails per replication) so that a total of 75 male broilers. The treatments were P0: drinking water without Vitamin E, Selenium and Zinc (control); P1: drinking water with 0,017 gram/kg body weight; P2: 0,033 gram/kg body weight; P3: 0,050 gram/kg body weight; P4: 0,067 gram/kg body weight. Based on the results of testing at the Laboratory of Veterinary Public Health, Lampung Disease Investigation Center, it was found that the carcasses of this study were of very good quality. This is evidenced from the results of all sample testing that meet the minimum requirements for quality, safe, healthy, intact and halal carcasses according to the standards set by the government in Standar Nasional Indonesia 7388:2009, including no changes in taste, smell, and consistency; no indication of decay by Durante and H2S tests; the total amount of microbial contamination is below the maximum limit (1x106 colonies/gram); and the amount of Eschericia coli contamination below the maximum limit of Standard Nasional Indonesia (1x102 colonies/gram). The conclusion indicates that the administration of the minerals Selenium, Zinc, and Vitamin E in drinking water can increase the stamina and endurance of broilers against infection and unfavorable environmental conditions during rearing, which can have an effect on the health of the broilers and the quality of the carcass produced. Keywords: Broiler carcass, Carcass quality, Selenium, Vitamin E, Zinc